2007
DOI: 10.1016/j.survophthal.2006.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and Eye Diseases

Abstract: The prevalence of obesity has reached epidemic proportions in many countries. While its impact on overall health is well documented, less is known about the ocular manifestations of obesity. Amongst different eye diseases, obesity has been linked with age-related cataract, glaucoma, age-related maculopathy, and diabetic retinopathy. Numerous population-based and prospective studies support an association between obesity and risk of age-related cataract. However, the nature and strength of these associations, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
230
4
4

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 309 publications
(250 citation statements)
references
References 232 publications
12
230
4
4
Order By: Relevance
“…Overweight and obesity are highly prevalent life-style disorders worldwide and are associated with various comorbidities (1-3), with a plethora of complications such as diabetic retinopathy, high intraocular pressure, cataracts, macular degeneration, and exophthalmos (4,5). Among these disorders, cataract is the leading cause of blindness worldwide and accounts for estimated cases of 18 million, half of all these cases originating in developing countries (6,7).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overweight and obesity are highly prevalent life-style disorders worldwide and are associated with various comorbidities (1-3), with a plethora of complications such as diabetic retinopathy, high intraocular pressure, cataracts, macular degeneration, and exophthalmos (4,5). Among these disorders, cataract is the leading cause of blindness worldwide and accounts for estimated cases of 18 million, half of all these cases originating in developing countries (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…Among these disorders, cataract is the leading cause of blindness worldwide and accounts for estimated cases of 18 million, half of all these cases originating in developing countries (6,7). Several large-scale population-based epidemiological studies consistently revealed strong links between obesity and cataract (5,(8)(9)(10)(11)(12). It is widely accepted that oxidative stress, osmotic stress, and nonenzymatic glycation of lens proteins are the primary mechanisms leading to cataract (13), and obesity might influence any or all of these physiological processes (14,15).…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Mechanical factors include an obesity-related increase in IOP. 30 OSAHS is often, although not invariably, associated with increased BMI. The positive association between obesity and intraocular pressure is proposed to be related to increased blood viscosity, increased episcleral venous pressure, and decreased aqueous outflow.…”
Section: Discussionmentioning
confidence: 99%
“…The positive association between obesity and intraocular pressure is proposed to be related to increased blood viscosity, increased episcleral venous pressure, and decreased aqueous outflow. 30 We did not have any patient in our cohort groups with disc swelling or pallor indicative of earlier episodes of ischemic optic neuropathy (NAION). Strong association of OSAHS with NAION has been shown in series of NAION patients when surveyed for symptoms of sleep disturbed breathing and/or on investigation with polysomnography.…”
Section: Discussionmentioning
confidence: 99%
“…In the medical literature, BMI had only been related to eye conditions linked to nutritional factors such as age-related macular degeneration or those related to the aqueous humour and intraocular pressure (IOP), but no statistical correlation was found (8,20) . Therefore, assessing the relationship between BMI and presbyopia is unprecedented in the literature.…”
Section: Discussionmentioning
confidence: 99%